Detection of adulteration and quality Evaluation of raw milk collected from Local markets in Bangladesh - Islam, Md. Anwarul; Sarker, Md. Touhiduzzaman; Prabakusuma, Adhita Sri; Russel, Md. Imrul Hasan; Islam, Md. Shahidul (Food Biology)
This experiment was aimed to detect adulteration and assess the quality of raw milk which were collected from various local markets in Bangladesh. The samples of the raw milk were collected from Narikali Bazar, Sofir Mia Bazar and Sokal Bazar of Jamalpur district in Bangladesh. Parameters were used to detect adulteration such as presence of Formalin, Starch, Cane Sugar, and coloring agent, and to screen the qualities of the samples on the basis of physical tests (color, flavor, taste, texture and specific gravity), chemical tests [acidity, fat, ash, lactose, protein, TS and SNF]-and microbiological tests. From the physical test, it was found that all the samples were yellowish white in color, normal in taste and flavor and free flowing fluid in case of texture. All of the raw milk samples did not fulfill the legal standard of milk composition. However, raw milk samples of Sokal Bazar were higher in fat, protein, lactose, SNF and TS contents than the other two samples. Microbiological parameters also remained high in all raw milk samples than the standard. It was observed that no adulteration was found in any of the collected raw milk samples. This study revealed that hygiene condition did not properly maintain during milking and transportation of the raw milk supplied in the local markets.